THE BIOLOGY OF CANADIAN WEEDS.: 81. Atriplex patula L., A . prostrata BOUCHER EX DC., AND A . rosea L. - BASSETT, I. J.; MUNRO, D. B. (Canadian Journal of Plant Science, 1987)
Atriplex patula L., spreading atriplex, A. prostrata Boucher ex DC., halberd-leaved atriplex, and A. rosea L., red scale, are introduced annual weeds occurring in gardens, fields and orchards in various parts of Canada. Red scale is expanding its range in western Canada where plants are abundant enough in some areas to cause hay fever from large amounts of pollen shed in late summer. Spreading atriplex occurs wide-ranging across Canada, it is rare in western Canada and occurs commonly from southern Ontario to Cape Breton Island; halbred-leafed atriplex has a similar distribution pattern but it occurs commonly throughout its range. Both can be weedy in small grains and gardens.Key words: Atriplex, orache, weed biology